Розслідування кримінальних правопорушень проти власності: типові слідчі ситуації та проблеми використання спеціальних знань - Степанюк, Р. Л.; Stepaniuk, R. L.; Гусєва, В. О.; Husieva, V. O.; Vlada Husieva; Степанюк Руслан (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 1. – С. 261-275, 2023)
Визначено, що основу будь-якої криміналістичної методики розслідування окремого виду чи групи кримінальних правопорушень становлять запропоновані алгоритми вирішення тактичних завдань початкового етапу розслідування в типових слідчих ситуаціях, а також специфіка проведення найбільш актуальних для відповідного виду або групи кримінальних правопорушень процесуальних дій і форми використання спеціальних знань. Установлено, що підставами для класифікації слідчих ситуацій початкового етапу розслідування кримінальних правопорушень проти власності можуть бути такі: 1) наявність і повнота інформації щодо особи, яка вчинила кримінальне правопорушення; 2) перспективи використання фактору раптовості в умовах, які склалися на момент початку досудового розслідування; 3) повнота наявних відомостей про подію кримінального правопорушення. Сформульовано проблемні питання, що виникають під час призначення товарознавчих, трасологічних, дактилоскопічних, портретних, молекулярно-генетичних експертиз, а також експертизи відео-, звукозапису у кримінальних правопорушеннях проти власності, наведено рекомендації щодо їх усунення.

During the period of the martial law regime, the legal system of Ukraine has undergone certain changes, as well as quantitative and qualitative indicators of crime. This has led to the fact that some criminal offences have become a significant part of the crime structure and have therefore become the focus of professional attention of law enforcement agencies. These include, inter alia, criminal offences against property, including theft, robbery, assault, extortion, fraud, misappropriation, embezzlement or misappropriation of property through abuse of office, and more. This has highlighted the need to ensure effective counteraction to such criminal offences. It has been substantiated that the basis of any forensic methodology for investigating a particular type or group of criminal offences is the proposed algorithms for solving tactical tasks of the initial stage of investigation in typical investigative situations, as well as the specifics of conducting the most relevant procedural actions and forms of using special knowledge for the relevant type or group of criminal offences. Typical investigative situations of the initial stage of investigation of criminal offences against property have been analysed. It has been established that the grounds for classification of investigative situations at the initial stage of investigation of criminal offences against property may be as follows: 1) availability and completeness of information about the person who committed the criminal offence; 2) prospects for using the factor of surprise in the conditions prevailing at the time of the beginning of the pre-trial investigation; 3) completeness of the available information about the criminal offence event. It has been noted that such an approach does not exclude the possibility of using other criteria, which in some cases may be of auxiliary importance in the construction of methodological and forensic recommendations. Based on the study of criminal proceedings, typical forensic examinations which are appointed in the course of investigation of criminal offences against property have been identified. It has been established that these include commodity, trace, fingerprint, portrait, molecular genetic, video and sound recording examinations. It has been identified the problematic issues arising in the course of their appointment, and recommendations have been formulated to eliminate the latter and improve the efficiency of implementation of this procedural form of use of special knowledge.

Определено, что основу какой-либо криминалистической методики расследования отдельного вида или группы уголовных правонарушений составляют предложенные алгоритмы решения тактических задач начального этапа расследования в типовых следственных ситуациях, а также специфика проведения наиболее актуальных для соответствующего вида или группы уголовных правонарушений процессуальных действий и формы использования специальных знаний. .
Investigation of criminal offences against property: typical investigative situations and problems of applying specialised knowledge
Keywords: досудове розслідування; криміналістична методика; привласнення, розтрата майна або заволодіння ним шляхом зловживання службовим становищем; слідча ситуація; судова експертиза; слідча (розшукова) дія; майно; зловживання службовим становищем; Україна; pre-trial investigation; forensic methodology; misappropriation, embezzlement or seizure of property by abuse of office; investigative situation; forensic examination; investigative (research) action; досудебное расследование; криминалистическая методика; присвоение, растрата имущества или завладение им путем злоупотребления служебным положением